COVID-19 and Global Beverage Markets: Implications for Wine. (May 2021) - Wittwer, Glyn; Anderson, Kym
Abstract: This article provides an empirical case study of the impacts of the COVID-19 pandemic on global beverage markets, particularly the wine sector. Both international trade and domestic sales have been adversely affected by temporary shifts away from on-premise sales by social distancing measures and self-isolation that led to the closure of restaurants, bars, and clubs, plus declines in international travel and tourism. Partly offsetting this has been a boost to off-premise and direct e-commerce sales. We first estimate those impacts in 2020 and their expected partial recovery in 2021 using a new model of global beverage markets. Further recent disruption to the global wine trade has been the imposition by China in late 2020 of prohibitive tariffs on its imports of bottled wine from Australia. Its diversionary and trade-reducing effects are compared with those due to COVID-19. (JEL Classifications: C63, D12, F14, F17, Q17)